Partner's survivorship care needs: An analysis in head and neck cancer patients. (August 2017) - Giuliani, Meredith; Milne, Robin; McQuestion, Maurene; Sampson, Lorna; Le, Lisa W.; Jones, Jennifer; Cheng, Terry; Waldron, John; Ringash, Jolie
Highlights: A significant proportion of partners experience unmet needs, which differ from the patient's needs. Increasing number of unmet needs in patients is significantly associated with increased unmet needs in their partners. The most common unmet partner needs were related to concerns about cancer returning, and coping with supporting someone with cancer, and the changes cancer has caused. Abstract: Purpose: To determine the number, type and predictors of unmet needs for head and neck cancer (HNC) survivors' partner's. Methods: Partners of HNC patients were invited to complete the Cancer Survivors' Partners Unmet Needs Survey (CaSPUN). Analysis determined number, proportion and factors associated with greater unmet needs using linear regression. Agreement between the unmet needs of patients and their partners was determined. Results: Among the 44 partners participated 29 reported ≥1 unmet need and 4 had a very high number of needs (31–35). The most common unmet needs were related to concerns about cancer returning, coping with supporting someone with cancer, and the changes cancer has caused. The highest reported needs were in the Relationships domain. Increasing patient unmet needs was significantly associated with increasing partner unmet needs (p < 0.01). Conclusions: A significant proportion of head and neck cancer partners experience unmet needs, which often differ from the patient's needs.